(untitled) (Journal of Informatics Education and Research, 2026)
Academic performance plays a vital role in the life of every student, as it determines their educational progress and future career prospects. As a result, many parents, teachers, guardians, students, and well-wishers are concerned about how students can improve their academic performance, which is a common concern worldwide. This emphasis on academic achievement has intensified expectations and has motivated extensive research in this area. Students’ success and their admission to schools and higher education institutions depend significantly on academic performance, just as employability plays an important role in an individual’s professional career. Consequently, it can be inferred that social media has a significant impact on senior secondary school students in many ways, particularly on their academic performance. This forms the basis of the research problem and the subject of the present study. In the contemporary digital era, social media has become an integral part of students’ daily lives, influencing their learning habits, study patterns, and academic engagement. Senior secondary students, in particular, spend a considerable amount of time on social networking platforms, which may either support or hinder their academic progress. The dual nature of social media—both as an educational resource and a potential distraction—makes it an important variable for systematic investigation. Understanding how social media usage affects students’ academic performance is essential for educators, parents, and policymakers. Therefore, the present study seeks to examine the nature and extent of the impact of social media on the academic achievement of senior secondary school students